Effect of PSI‐697, a Novel P‐Selectin Inhibitor, on Platelet–Monocyte Aggregate Formation in Humans. Issue 1 (28th January 2013) - Japp, Alan G.; Chelliah, Raj; Tattersall, Laura; Lang, Ninian N.; Meng, Xu; Weisel, Kathleen; Katz, Arie; Burt, David; Fox, Keith A. A.; Feuerstein, Giora Z.; Connolly, Thomas M.; Newby, David E.
Abstract : Background: Platelet activation is central to the pathogenesis of acute coronary syndromes. Surface expression of P‐selectin on activated platelets induces formation of platelet–monocyte aggregates and promotes vascular inflammation and thrombosis. P‐selectin antagonism may represent a novel therapeutic strategy in vascular disease. We aimed to investigate the effects of the novel P‐selectin antagonist PSI‐697 on platelet–monocyte aggregate formation in humans. Methods and Results: In a double‐blind, randomized, placebo‐controlled crossover study, healthy smokers were randomized to receive either oral PSI‐697 600 mg or matched placebo. The sequence of treatment was also randomized, with all subjects receiving both PSI‐697 and placebo. Platelet–monocyte aggregates were measured by flow cytometry at 4 and 24 hours in the presence and absence of thrombin receptor‐activating peptide (TRAP; 0.1 to 1.0 μm/L). The ex vivo addition of TRAP caused a concentration‐dependent increase in platelet–monocyte aggregates from 8.2% to 94.8% ( P <0.001). At 4 and 24 hours, plasma concentrations of PSI‐697 increased to 1906 and 83 ng/mL, respectively ( P <0.001). PSI‐697 had no demonstrable effect on either stimulated or unstimulated platelet–monocyte aggregates at 4 or 24 hours ( P >0.05). P‐selectin‐blocking antibody (CLB‐Thromb6), but not PSI‐697, inhibited both stimulated and unstimulated platelet–monocyte aggregate formation in vitro ( P <0.001). Conclusions: The novel small‐molecule P‐selectin antagonist PSI‐697 did not inhibit basal or stimulated platelet–monocyte aggregate formation in humans at the dose tested. Its clinical efficacy remains to be established. Clinical Trial Registration: URL:http://EudraCT.ema.europa.eu Unique identifier: 2007‐005695‐14.